PERAN HUKUM DALAM MENEKAN PRAKTEK PERNIKAHAN DINI SEBAGAI SALAH SATU PENGHAMBAT PERKEMBANGAN EKONOMI - Hadi Nur Ikhwan; Nuzulia Kumala Sari (PT. Hasba Edukasi Mandiri, 2025)
Early marriage is the marriage of a minor. Each country has different age limits for what constitutes a child. According to the United Nations Population Fund (UNFPA), early marriage is a marriage in which both the bride and groom, or one of them, are under 18 years of age. This concept aligns with the Convention on the Rights of the Child, which defines a child as a child if they are under 18. Early marriage occurs in almost every corner of the world, particularly in developing countries. Various backgrounds and reasons underpin early marriage, including ingrained culture, parental mindset, religion, economics, and various other factors. Factors driving the occurrence of unregistered marriages in Indonesia, particularly in developing societies, include the negative perception of spinsterhood if not married after the age of 17, or the practice of marrying between the ages of 14 and 16. Parents hope to receive support from their children after marriage due to limited family finances. Factors influencing the average age of women's first marriage include social, economic, and residential factors (Population and Family Planning Agency, 2012). The research method used in this journal article is normative-juridical. The Policy Research approach, proposed by Ann Majchrzak (1984), defines analyzing emerging social problems so that the findings can be recommended to decision-makers for practical action to resolve them. The research approach is a plan and procedure that defines the steps in data collection, analysis, and interpretation. Law Number 16 of 2019 clearly prohibits underage marriage. Article 1, number 1 of Law Number 23 of 2002 concerning Child Protection, defines a child as a person under 18 (eighteen) years of age, including unborn children. The Constitutional Court of the Republic of Indonesia has issued Constitutional Court Decision Number 22IPUU-XV/2017, one of the considerations of the Constitutional Court in the decision being,